PENGARUH KUALITAS PELAYANAN DAN PROMOSI DIGITAL TERHADAP LOYALITAS PELANGGAN XLSMART DI KABUPATEN CIANJUR - Nuralia Aldawiyah; Muhahammad Sahlan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study is motivated by the increasing competition in the telecommunications industry, which requires companies not only to provide high-quality services but also to utilize digital promotion effectively in order to maintain customer loyalty. In the digital era, service quality and digital promotion play an important role in building long-term relationships with customers. XLSmart , as one of the telecommunications service providers in Cianjur Regency, implements service quality improvement and digital promotion strategies to enhance customer loyalty. The purpose of this study is to examine the effect of service quality and digital promotion on customer loyalty at XLSmart in Cianjur Regency. This research employs a quantitative method with descriptive and verificative approaches. Data were collected through questionnaires distributed to active XLSmart customers. The sample was determined using the Slovin formula, resulting in 100 respondents. Data analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-test, and F-test using SPSS version 25. The results indicate that service quality and digital promotion have a positive and significant effect on customer loyalty, both partially and simultaneously. Therefore, it can be concluded that improving service quality and implementing effective digital promotion strategies are able to enhance and sustain customer loyalty at XLSmart in Cianjur Regency.